If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=3(Y+5)(Y+2)
We move all terms to the left:
-(3(Y+5)(Y+2))=0
We multiply parentheses ..
-(3(+Y^2+2Y+5Y+10))=0
We calculate terms in parentheses: -(3(+Y^2+2Y+5Y+10)), so:We get rid of parentheses
3(+Y^2+2Y+5Y+10)
We multiply parentheses
3Y^2+6Y+15Y+30
We add all the numbers together, and all the variables
3Y^2+21Y+30
Back to the equation:
-(3Y^2+21Y+30)
-3Y^2-21Y-30=0
a = -3; b = -21; c = -30;
Δ = b2-4ac
Δ = -212-4·(-3)·(-30)
Δ = 81
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{81}=9$$Y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-21)-9}{2*-3}=\frac{12}{-6} =-2 $$Y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-21)+9}{2*-3}=\frac{30}{-6} =-5 $
| 3xx-5x+2=0 | | 9(x-5)=-18.9 | | 2(a-8)=20.4 | | k^2+5k+31=0 | | 10=6c-5 | | 8e-6=51.6 | | 6(a+3)=54 | | 104=8x-16 | | 5+8x=109 | | 14x+8=-5x-9 | | x+7=-82 | | 7(7(x−4)=5(x+8) | | 8w=5760w= | | 2z-3z-11z=-4(6) | | 3x*x=30 | | 0.78g+0.5g-1.89=0.67 | | x-7=12+2 | | 2(1)+0.2y=0.2 | | y+2+7y–3=15 | | 3x~2.4=9.6 | | 16x+84=90 | | 16x-6=45 | | -6x+11=-61 | | 9h-17=63 | | x+32=3(4x-4) | | 5(x-3)-4=21 | | 3(x+4)+9=-x+25 | | -46=2(3x-2) | | -43=3(4x-1)-4 | | -4=2(3x-1)-8 | | 4x-29=7x-59 | | 2(5x-2)=2x-20 |